Zoosynteza, czyli mocny słaby podmiot. Anna Barcz: Realizm ekologiczny. Od ekokrytyki do zookrytyki w literaturze polskiej. Katowice, Wydawnictwo Naukowe „Śląsk”, 2016, ss. 365 - Krupiński, Piotr (Narracje o Zagładzie [czasopismo zamknięte], 2017)
Zoosynthesis, or a Strong Weak Subject. Anna Barcz: Realizm ekologiczny. Od ekokrytyki do zookrytyki w literaturze polskiej. Katowice, Wydawnictwo Naukowe „Śląsk”, 2016, ss. 365. This article is a review of – or, to be more precise, an attempt to critically discuss – Anna Barcz’s monograph Realizm ekologiczny. Od ekokrytyki do zookrytyki w literaturze polskiej. This vast work is entirely focused on tracing ecocritical and pre‑ecocritical contexts in Polish literature, and thereby it offers the readers a new look at the canon of Polish modern literature. Yet, the value of Anna Barcz’s monograph lies in something more. This book successfully implants new directions of the literary studies (mainly from the Anglo‑American humanities), showing the usefulness of ecocriticism and zoocriticism as the tools that help understand more fully not only texts of culture but also the surrounding world: the world within which the human “I” does not have to be the only source of experience.